أسلوب مقترح لحل المنازعات الناتجة عن اختلاف كمية التسليح - مصطفى ماهر (Latakia University Journal -Engineering Sciences Series, 2019)
تتسم صناعة التشييد بكثرة المنازعات والمشاكل وذلك بسبب تعقيد هذه الصناعة وتعدد الأطراف المشاركة فيها. ومن الطبيعي أن تؤثر المنازعات على إدارة مشروع التشييد وتؤدي لزيادة الانحرافات في خطة المشروع سواء بالنسبة لزمن التنفيذ أو كلفته. وتأتي المنازعات بسبب اختلاف كميات التسليح مابين مستندات التعاقد وواقع التنفيذ في مقدمة هذه المشاكل، وقد ظهرت هذه المشكلة أكثر بعد الإرتفاع العالمي في أسعار الطاقة وزيادة الطلب على هذه المادة نتيجة التوسع في المشاريع العملاقة وانعكاس ذلك بشكل مباشر على سعر حديد التسليح. في هذا البحث تم رصد معظم الأسباب التي تؤدي إلى إختلاف كميات حديد التسليح مابين مستندات التعاقد وواقع التنفيذ وتم تصنيفها إلى أسباب تتعلق بالدارس وأسباب تتعلق بالمقاول وأسباب تتعلق بجهاز الإشراف. وتم عرض دراسة حالة لأحد المشاريع وبعد ذلك تم تقديم الأسلوب المقترح عن طريق معالجة المشكلة عبر مراحل عمر المشروع. Construction industry has many features, such as complexity and multiplicity of participants. As a result of these features, many problems will occur and affect the management of a construction project. These problems will increase variations in time and cost. One of these problems is the difference in reinforced steel quantity between contract documents and implementation on a construction site, especially after an international increase in oil prices and an increasing international demand for reinforced steel. These reasons bring about a rise in the prices of reinforced steel. This research identifies most of the reasons leading to variations between contract documents and implementation on a construction site. These reasons are classified into ones related to consultant, contractor, and engineer. A case study of one of projects is presented. Then, a proposed technique is presented for handling this problem throughout a project’s time span.